A Compressive Damage Constitutive Model for Rock Mass with a Set of Nonpersistently Closed Joints under Biaxial Conditions. (24th March 2015) - Liu, Hongyan; Yuan, Xiaoping
Abstract : One of the most problems faced by the practical rock engineering is to evaluate the rock mass strength. Now the existing theoretical evaluation of the mechanical property of jointed rock mass has no satisfactory answer yet because of the great number of variables involved. One of them is the nonpersistent joints which inherently affect the rock mass mechanical behavior. The previous models for rock mass can only reflect the effect of joint geometrical property on its mechanical behavior. Accordingly, this paper presents a new theoretical model to evaluate the mechanical behavior of the rock mass with a set of nonpersistently closed joints under biaxial conditions, which can reflect the effect of both the joint geometrical and mechanical property on the mechanical behavior of the rock mass under biaxial conditions at the same time. A series of calculation examples validate that the proposed model is capable of presenting the effect of joint geometrical and mechanical properties and the confining pressure on rock mass strength at the same time.